Sensitivity and Generalized Sensitivity Studies of the SIR and SEIR Models of Computer Virus: SIR and SEIR Model of Dynamics of Computer Virus - Munir, Mohammad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this article, the sensitivity and generalized sensitivity analyses of the SIR and SEIR models of the dynamics of computer virus is presented. From the sensitivity studies of the SIR model, it follows that both the parameters in the model affect the model output in the beginning. The sensitivity of the SEIR model shows that the susceptible computers in the network are affected majorly by the rate at which external computers are connected to the network and the recovery rate of the susceptible computer due to the anti-virus ability of the network. From the generalized sensitivity of the SIR model, it follows that both the infected rate and the recovery rate are sensitive in the beginning and are highly correlated. The generalized sensitivities of the SEIR model show that the recovery rate of the infected computers that are cured is insensitive with respect to the measurements from all compartments.